THE EFFECT OF EDUCATIONAL UNITS ACCORDING TO LEARNING STATIONS OF VARYING LEVELS ON IMPROVING COGNITIVE MOTIVATION AND GOALSCORING IN FOOTBALL - DHARI SALMAN RASHID (Proximus Journal Publishing, 2025)
The research aimed to develop educational units based on learning stations of varying difficulty levels to improve cognitive motivation and goal-scoring in football, It also aimed to identify differences between pre- and post-test results in the variables of scoring from a stationary position and scoring from movement for the three research groups, The researcher used the experimental method as it was suitable for the nature of the problem , The researcher relied on a sample of players from Al-Kadhimiya Sports Club (youth category), aged 17-19, totaling (18) players, who were selected purposively, This sample represented (11%) of the original population of (200) players representing (10) clubs in Baghdad, The research sample was divided into three groups by lottery as follows: the first experimental group, consisting of (6) players, which worked according to the learning stations of varying difficulty levels; the second experimental group, consisting of (6) players, which worked according to the delegation method in setting its goals; and the third (control) group, consisting of (6) players, which worked according to the coach's method, The positive impact of the educational units that were implemented on the experimental groups (first and second) had a significant effect on improving the cognitive motivation and goal-scoring of the young players.
Keywords: Educational units; diverse learning stations; cognitive motivation